Demand and Supply Factors in the Determination of NIE Exports: A Simultaneous Error-Correction Model for Hong Kong Exports. - Muscatelli, V; Srinivasan, T; Vines, D (CEPR, 1992)
This paper considers the issue of whether a small developing economy such as Hong Kong faces a perfectly elastic demand for its exports of manufactured goods. We construct a simultaneous demand and supply system which is estimated using Full Information Maximum Likelihood methods, and which allows us to clearly identify demand and supply factors in determining export volumes and prices. Our empirical findings differ from previous studies conducted with this data set in that they suggest that even a small dynamic newly industrialized economy such as Hong Kong may not face infinitely elastic demand for its manufactured goods. We also advance some reasons to explain why the 'small country assumption' may not be applicable in the case of most industrialized economies.